2021
DOI: 10.5039/agraria.v16i2a8902
|View full text |Cite
|
Sign up to set email alerts
|

Technological characterization of particleboards constituted with pistachio shell (Pistacia vera) and Pinus oocarpa wood

Abstract: The objective of this work was to produce and characterize particleboards manufactured with pine wood and pistachio shell. Three mix proportions of 25, 50 and 75% were used, and for the control, panels manufactured with 100% pistachio shell were adopted. The panels were produced with a nominal density of 0.75 g cm -3 . The properties analyzed were: apparent density, water absorption, thickness swelling, modulus of rupture, modulus of elasticity and perpendicular traction. The chemical characterization of the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 12 publications
0
1
0
Order By: Relevance
“…In other studies, this variation in density in relation to the panel nominal density was also found and was attributed the loss of inputs (adhesive, paraffin and particles) during the panel manual production, as well the volume increase of the panels after hot pressing and packaging (BRITO et al, 2021;BAZZETTO et al, 2019;GUIMARÃES JÚNIOR et al, 2016). There was a difference in the thickness of the panels caused by a return in relation to the nominal thickness of the limiting bars.…”
Section: Panel's Physical Propertiesmentioning
confidence: 63%
“…In other studies, this variation in density in relation to the panel nominal density was also found and was attributed the loss of inputs (adhesive, paraffin and particles) during the panel manual production, as well the volume increase of the panels after hot pressing and packaging (BRITO et al, 2021;BAZZETTO et al, 2019;GUIMARÃES JÚNIOR et al, 2016). There was a difference in the thickness of the panels caused by a return in relation to the nominal thickness of the limiting bars.…”
Section: Panel's Physical Propertiesmentioning
confidence: 63%
“…who reported an average of 6,18 % andBrito et al (2021) who obtained an average of 6,34 %. The higher value is considered ideal, because the lignin contributes to the adhesion mechanisms and may contribute to the bonding process of the panels.Regarding the ash,Santos et al (2022) have found a content of 1,20 % close to the present study.…”
mentioning
confidence: 95%